PENYULUHAN CUCI TANGAN TERHADAP PERILAKU HIDUP BERSIH DAN SEHAT DI SDS GALILEA HOSANA PADANG BULAN SELAYANG KECAMATAN MEDAN SELAYANG - Sebayang, Julenda; Surjani, Lylys; Tambunan, Ronald T. H.; Situmorang, Nasib M.; Simanjuntak, Salomo G. U.; Gumelar, Arum Geger; Hulu, Elvani L. S.; Berutu, Grace A.; Butarbutar, Fransiska A.; Saruksuk, Atta C. N.; Simanjuntak, Donitha R.; Zebua, Agung K.; Sianipar, Pebrina; Manik, Horas Rejeki; Wiliam, Wiliam (Jurnal Pengabdian Pada Masyarakat METHABDI, 2023)
PHBS stands for Clean and Healthy Living Behavior, aiming in the health sector to cultivate clean and healthy living behavior in the form of individuals, groups or the wider community. PHBS must be cultivated especially to children, for example through educational institutions. The purpose of counseling is carried out to prevent the disease is that children are taught to wash their hands. The counseling was conducted at Galilee Hosana School, Jl. Bunga Terompet No.30, Padang Bulan Selayang II, Kec. Medan Selayang, Medan City on December 6, 2023. As a result, 4th grade students of SDS Galelia Hosana can understand and practice hand washing properly and correctly. So it can be concluded that PHBS counseling on hand washing practices in grade 4 students is useful and important for health.